IMPLEMENTASI PEMBELAJARAN BERBASIS TEKS DALAM MENINGKATKAN LITERASI AKADEMIK MAHASISWA PASCASARJANA BAHASA INDONESIA - Arif Rahman; Muhammad Rifki; Darwin Effendi; Hetilaniar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of text-based learning in improving the academic literacy of postgraduate students in the Indonesian Language Study Program. Academic literacy at the postgraduate level encompasses the ability to read, write, and think critically systematically in an academic context. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that text-based learning significantly contributes to improving students' academic literacy. Students are able to understand academic texts more deeply, organize scientific information, and produce academic writing that aligns with scientific conventions. Text-based learning emphasizes understanding the structure, social purpose, and linguistic characteristics of texts, enabling students to actively engage in the process of analyzing and producing scientific texts. In addition to improving technical skills, this approach also builds students' academic awareness and critical thinking skills. Despite challenges related to differences in students' initial abilities and time constraints, text-based learning has proven to be an effective and sustainable strategy for strengthening the academic literacy of postgraduate students in Indonesian Language. This research has implications for the development of more contextual and practice-based learning methods in higher education.